Endoscopic Excision of Hip Heterotopic Ossification, Plus Indomethacin and Radiation, Is Effective in Treating and Preventing Recurrence - Taylor Wingo, M.D; Dhruv S. Shankar, B.S; Anthony A. Essilfie, M.D; Thomas Youm, M.D (Elsevier, 2023)
Purpose: To describe the clinical and patient-reported outcomes of heterotopic ossification (HO) excision as well as the results of a standardized HO prophylaxis protocol among a group of patients who previously underwent open or arthroscopic hip surgery. Methods: Patients who developed HO after index hip surgery and were subsequently treated with arthroscopic excision of HO and postoperative HO prophylaxis using 2 weeks of indomethacin and radiation were retrospectively identified. All patients were seen by a single surgeon and were treated with the same arthroscopic technique. Patients were also placed on a regimen of 2 weeks of indomethacin 50 mg and radiation therapy with 700 cGy in one fraction on the first postoperative day. Outcomes assessed included recurrence of HO and conversion to total hip arthroplasty by latest follow-up. Other outcomes included Modified Harris Hip Scores and Non-Arthritic Hip Scores, which were collected preoperatively and at 1-year and 2-year follow-up. Results: There were 5 female and 9 male subjects, with an average age of 39 years (range 22-66) and average body mass index of 27.1 (19.1-37.5). Average follow-up time was 46 months (range 4-136). No patients had experienced HO recurrence by latest follow-up. Only 2 patients converted to total hip arthroplasty, one at 6 months and the other at 11 months postexcision. Average outcome scores improved by 2-year follow-up (average Modified Harris Hip Scores 52.8 improved to 86.5, average Non-Arthritic Hip Scores 49.4 improved to 83.8). Conclusions: Minimally invasive arthroscopic excision of HO and postoperative prophylaxis with combined indomethacin and radiation therapy effectively treats and prevents the recurrence of HO. Level of Evidence: Level IV, case series, therapeutic.